Analisis Cash Flow Volatility, Sales Volatility, Leverage dan Earning Persistence - Sunaryo -; Humaeroh - (AKRUAL : Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of cash flow volatility, sales volatility, and leverage on earning persistence in Consumption sector companies listed on the indonesia stock exchange for the 2017-2020 periode. Samples taken using the purpose sampling method. The type of data used is secondary data sourced from the indonesia stock exchange website. The population in this reseacrh are Consumption sector companies listed on the indonesia stock exchange for the 2017-2020 periode. From a population of 51 Consumption sector companies, 25 companies were obtained as samples with an observation period of 4 years (2017-2020). The data analysis method used is multiple linear regression analysis. Based on the results of the research show that the cash flow volatility have a positive and significant effect on earnings persistence, sales volatility have a positive and significant effect on earnings persistence and leverage have a positive and significant effect on earnings persistence.